Photocatalytic degradation on Disperse Blue with nano-TiO2 film electrode. (1st January 2013) - Tang, Wenwei; Wu, Lujun; Chen, Xiaoying; Zeng, Xinping
Sol-gel method was used to prepare anatase-TiO2 electrode, and its photocatalytic characteristics were investigated under UV light for the degradation of Disperse Blue. The resulting composite photocatalysts were characterised by the X-ray diffraction (XRD), and scanning electron microscopy (SEM). The optimisation of parameters for preparation of electrode was also investigated. The results showed that 0.05 mL ethanolamine as the proper volume for sol system, 15 times' coating, 90 min as the optimal annealing time and 500°C as the optimal annealing temperature was chosen for preparation of electrode. The prepared nano-TiO2 electrode is used for degradation of 100 mg/L DB solution under UV light and the result showed that the decolourisation rate is more than 90% within 30 min.